Enhanced infarct myocardium repair mediated by thermosensitive copolymer hydrogel-based stem cell transplantation. (May 2015) - Xia, Yu; Zhu, Kai; Lai, Hao; Lang, Meidong; Xiao, Yan; Lian, Sheng; Guo, Changfa; Wang, Chunsheng
Mesenchymal stem cell (MSC) transplantation by intramyocardial injection has been proposed as a promising therapy strategy for cardiac repair after myocardium infarction. However, low retention and survival of grafted MSCs hinder its further application. In this study, copolymer with N-isopropylacrylamide/acrylic acid/2-hydroxylethyl methacrylate-poly(ɛ-caprolactone) ratio of 88:9.6:2.4 was bioconjugated with type I collagen to construct a novel injectable thermosensitive hydrogel. The injectable and biocompatible hydrogel-mediated MSC transplantation could enhance the grafted cell survival in the myocardium, which contributed to the increased neovascularization, decreased interstitial fibrosis, and ultimately improved heart function to a significantly greater degree than regular MSC transplantation. We suggest that this novel hydrogel has the potential for future stem cell transplantation.